(untitled) (Research, Society and Development, 2022)
Objective: To investigate the influence of intraradicular moisture conditions on the bond strength of 3 different endodontic cements in the coronal, middle, and apical thirds of the root canal. Materials and Methods: 90 single-rooted teeth were instrumented with a reciprocal R#50 file and randomly divided into 3 experimental groups: Dry group: dry canals with absorbent paper tips; Moist group: suction syringe and capillary tip coupled to a vacuum pump; Wet group: aspiration with endodontic suction. The groups were divided according to the endodontic sealer used: AH plus (Denstply), Hiflow (Brasseler) and Bio-c Sealer (Angelus). Obturation was performed using Tagger’s hybrid technique with a single cone. The teeth were subjected to the "push-out" test to evaluate the bond strength of the cements. Results: Data were analyzed using the Kolgomorov-Smirnoff normal distribution test and the Mann Whitney U test to compare means within and between groups. The standard error established was 5% at a significance level of 95%. AH plus showed better results regardless of canal moisture conditions. Hiflow showed better bond strength in the dry group compared to the moist group (p=0.023) in the cervical area. Bio-C Sealer showed no statistically significant differences (p > 0.05). Conclusion: Moisture conditions affected the bond strength values of endodontic cements. The prevalence of failure moduli was mixed in all root thirds, regardless of the cement used.